A Study of Phytopharmacognostic and Clinical Efficacy of Palasha Beeja (Butea Monosperma Lan-Kutze) in Prameha w.s.r. to Diabetes Mellitus-II (AYUSHDHARA, 2025)
Prameha Vyadhi, known as Type 2 Diabetes Mellitus in contemporary science, is classified as one of the Ashtamahagadas due to its chronic nature and involvement of Tridoshas and Dasha Dushya. It is considered Kruchrasadya or Yapya, emphasizing the need for maintaining proper control and management to avoid complications. Ayaskriti, categorized under Arishta Kalpana, possesses Katu-Tikta-Kashaya Rasa and Laghu, Ruksha, Teekshna Guna, which provide Deepana-Pachana properties and aid in Kapha-Kleda-Medo Upashoshana, essential in the treatment of Prameha. This study evaluates the efficacy of Palasha Beeja Ghana Vati as Abhyantara Shamana Chikitsa in the management of Prameha. Aims and Objectives: 1. To assess the efficacy of Palasha Beeja Ghana Vati (Butea monosperma Lam.-Kuntze) in Prameha, with special reference to Type 2 Diabetes Mellitus. 2. To conduct a preliminary phytochemical evaluation of Palasha Beeja. 3. To analyze the pharmacognostic properties of Palasha Beeja Ghana Vati in Prameha Vyadhi. Materials and Methodology:  This is a clinical study with pre-test & post-test design. A total of 40 patients diagnosed with Prameha were selected, irrespective of sex, religion, occupation, or economic status. Intervention: Trail Group: Patient were administered with Palasha Beeja Ghana Vati- 500mg twice a day, before food. Observations and Results: The effect of the treatment was assessed on before the treatment and after the treatment by applying Wilcoxon’s rank sum test within the group respectively. It was Seen the treatment with Palasha Beeja Ghana Vati was effective in treating Prameha Vyadhi. Discussions and Conclusion: The study can be concluded from the study that in the management of Prameha, the Shamana Chikitsa with Palasha Beeja Ghana Vati (Butea monosperma Lan-Kutze) was effective and plays an important role in Prameha.